Intensitas Frekuensi dan Kekuatan Gempa yang Terjadi di Kota Bengkulu Tahun 2018-2023 - Edwar; Wira Citra, Fevi; Silaban, Nurmintan; Anggun Dwi Utami; Citra, Fevi Wira (Jurnal Georafflesia : Artikel Ilmiah Pendidikan Geografi, 2024)
The city of Bengkulu, which is located on the southwest coast of Sumatra Island, Indonesia, is located in an area with quite high seismic activity. This region has a history of earthquakes and is prone to seismic events because it is located on a major fault line. The earthquakes that occurred in Bengkulu City in the 5 year period from 2018 to 2023, namely in 2018 there were 8 earthquakes, in 2019 there were 16 earthquakes, in 2020 there were 6 earthquakes, and in 2021 Until 2023 there will be 1 earthquake. Understanding the characteristics and impacts of earthquakes in Bengkulu City is very important in disaster preparedness and mitigation efforts. It is important for citizens and authorities to be aware of the potential risks associated with earthquakes and take appropriate action to ensure public safety. This includes implementing building codes and regulations that prioritize earthquake-resistant construction practices and conducting public awareness campaigns to educate the public about earthquake preparedness and response strategies.